Neuropathic Pain Creates an Enduring Prefrontal Cortex Dysfunction Corrected by the Type II Diabetic Drug Metformin But Not by Gabapentin - Shiers, Stephanie (J Neurosci, 2018)
Chronic pain patients suffer from pain-related cognitive deficits, even when taking commonly prescribed analgesics. These deficits are likely related to pain-related maladaptive plasticity in the frontal cortex. We sought to model cognitive deficits in mice with neuropathic pain to examine maladaptive morphological plasticity in the mPFC and to assess the effects of several therapeutics. We used an attentional set-shifting task in mice with spared nerve injury (SNI) who received either a single intrathecal injection of an analgesic dose of clonidine, 7 d of 100 mg/kg gabapentin, or 7 d of 200 mg/kg metformin. Male SNI mice were significantly more impaired in the set-shifting task than females. This deficit correlated with a loss of parvalbumin (PV) and reductions in axon initial segment (AIS) length in layers 5/6 of the infralimbic (IL) cortex. Acute pain relief with clonidine had no effect on set-shifting performance, whereas pain relief via 7 day treatment with gabapentin worsened the impairment in both SNI and sham mice. Gabapentin reversed the PV loss in the IL but had no effect on AIS length. Treatment with the AMPK-activator metformin completely reversed the pain-related cognitive impairment and restored AIS length in the IL but had little effect on PV expression. Our findings reveal that neuropathic pain-related cognitive impairments in male mice are correlated to bilateral morphological changes in PV interneurons and layer 5/6 IL pyramidal neuron AIS. Pain relief with metformin can reverse some of the functional and anatomical changes. SIGNIFICANCE STATEMENT Cognitive impairments are a comorbidity of neuropathic pain but are inadequately addressed by existing therapeutics. We used a neuropathic pain model in mice to demonstrate that male (but not female) mice show a robust pain-related deficit in attentional set-shifting, which is associated with structural plasticity in axon initial segments in the infralimbic cortex. These deficits were completely reversed by 7 day treatment with the antidiabetic drug metformin, suggesting that this drug can be repurposed for the treatment of neuropathic pain and its cognitive comorbidities. Our findings have implications for our understanding of how neuropathic pain causes structural plasticity in the brain, and they point to a marked sexual dimorphism in neuropathic pain mechanisms in mice.